2021
DOI: 10.1186/s12964-021-00738-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA leakage induces odontoblast inflammation via the cGAS-STING pathway

Abstract: Background Mitochondrial DNA (mtDNA) is a vital driver of inflammation when it leaks from damaged mitochondria into the cytosol. mtDNA stress may contribute to cyclic GMP-AMP synthase (cGAS) stimulator of interferon genes (STING) pathway activation in infectious diseases. Odontoblasts are the first cells challenged by cariogenic bacteria and involved in maintenance of the pulp immune and inflammatory responses to dentine-invading pathogens. In this study, we investigated that mtDNA as an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…Moreover, we found that leaked cytosolic mtDNA acts as a DAMP to activate the NLRP3 inflammasome, causing pyroptosis and intensifying inflammation in odontoblast-like cells. From our previous [ 11 ] and present study, cytosolic mtDNA promotes pulp inflammation through the pyroptosis pathway and the STING pathway, suggesting that protecting mitochondria and reducing mtDNA leakage under inflammatory stimuli can delay the progression of inflammation. To further explore the relationship between these two signaling pathways, we found that the STING pathway was compensatorily activated after GSDMD knockdown.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Moreover, we found that leaked cytosolic mtDNA acts as a DAMP to activate the NLRP3 inflammasome, causing pyroptosis and intensifying inflammation in odontoblast-like cells. From our previous [ 11 ] and present study, cytosolic mtDNA promotes pulp inflammation through the pyroptosis pathway and the STING pathway, suggesting that protecting mitochondria and reducing mtDNA leakage under inflammatory stimuli can delay the progression of inflammation. To further explore the relationship between these two signaling pathways, we found that the STING pathway was compensatorily activated after GSDMD knockdown.…”
Section: Discussionsupporting
confidence: 63%
“…Human dental pulp tissue was collected as described above [ 11 , 19 ] and separated into two groups: 16 healthy teeth and 16 pulpitis teeth. The healthy group included no history of dental pulp disease and no oral diseases, such as dental caries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All images were analyzed by ImageJ software. Mitochondrial reactive oxygen species (mitoROS) were determined using MitoSOX as previously described ( Zhou et al, 2021 ). Briefly, the cells were incubated with 5 µM MitoSOX for 10 min at 37°C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with nDNA, mtDNA is more unstable and vulnerable to the effects of oxidative stress due to its proximity to mitochondrial reactive oxygen species (mtROS) and a lack of repair machinery. mtDNA stress may contribute to the cGAS-STING pathway activation and type 1 interferon responses in various pathological states, including infectious diseases, cancer, neurodegeneration, and other mitochondria-related illnesses (Zhou et al, 2021 ). Importantly, it has been established that mtDNA depletion inhibited the cGAS-STING pathway and nuclear translocation of p65 and IRF3 (Zhou et al, 2021 ).…”
Section: The Activators Of the Cgas-sting Pathway In Chronic Painmentioning
confidence: 99%